2013
DOI: 10.4193/rhino12.045
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-induced rhinitis

Abstract: Background: Pregnancy-induced rhinitis (PIR) is often misclassified and under-diagnosed. There is currently no cure or optimum symptomatic treatment. Objective: To summarize current knowledge of PIR and assess evidence supporting treatment options. Type of review: Structured literature search. SEARCH STRATEGY AND EVALUATION METHOD: Review of English-language articles addressing evidence for aetiology, classification, differential diagnosis or treatment options for PIR. Comparisons to management of other type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 64 publications
(76 reference statements)
2
51
0
Order By: Relevance
“…Regarding risk factors for the development of gestational rhinitis, smoking was the only one identified with significant evidence. 7 , 16 The same study found that the specific IgE to house dust mites was a predisposing factor for the development of the disease. 16 There is no association between gestational rhinitis and pre-existing asthma.…”
Section: Etiology and Physiopathogenymentioning
confidence: 89%
See 4 more Smart Citations
“…Regarding risk factors for the development of gestational rhinitis, smoking was the only one identified with significant evidence. 7 , 16 The same study found that the specific IgE to house dust mites was a predisposing factor for the development of the disease. 16 There is no association between gestational rhinitis and pre-existing asthma.…”
Section: Etiology and Physiopathogenymentioning
confidence: 89%
“… 8 Also, no association was observed with maternal age, gestational age, child's gender, and parity. 1 , 7 , 17 In relation to the actual allergic rhinitis, it was observed that the electron microscopy findings in pregnant women with nasal symptoms were identical to those with allergic rhinitis. 18 …”
Section: Etiology and Physiopathogenymentioning
confidence: 98%
See 3 more Smart Citations